The strategies of Portuguese civil society organizations in the field of the environment - Brito, Brígida (2014)
“The strategies of civil society organizations in the field of the environment” is the result of research conducted as part of the Project “strategies of international players in the area of the environment” carried out at OBSERVARE, the Observatory for External Relations of Universidade Autónoma de Lisboa. The objective of the study was to understand and characterize the involvement of Portuguese NGOs, or of those based in Portugal, in the field of the environment, identifying and evaluating the relationships they have established with external partners, namely with regard to the following: privileged countries; types of partners; intervention areas; methodologies and tools. The study was based on the concepts of development cooperation, including players and tools, partnership in international relations, and social and environmental sustainability, taking also into account the Millennium Development Goals, in particular as regards the Seventh Target: Guaranteeing Environmental Sustainability. Given the broad scope of the study, a short questionnaire was built following the principle of guaranteed anonymity and made available online. After making a list of NGOs (ENGOs and DNGOs), the questionnaire was sent to many of these organizations, requesting them to respond to the questionnaire (N=43). From the data analysis and by confronting it with the concepts previously explored, it emerged that the majority undertake joint activity in Portugal and in partner countries, mostly with other similar organizations after the establishment of partnerships. The activity focuses on social and environmental projects of local relevance, with mixed funding that is mostly international in nature, and has clear objectives for promoting development.